Automation of gearbox design - Fürst, Marius; Götz, Joshua; Otto, Michael; Stahl, Karsten (Forschung im Ingenieurwesen, 2022)
In order to respond to a shortened development time of today’s transmission systems, the automation of certain steps in the design process is essential for ensuring an efficient development process. Computer-aided tools are widely used for analyzing given design configurations because standardized methods are available to evaluate the load carrying capacity of all key components of a simple gear train, namely bearings, shafts and gears. At an early stage of development, requirements and restrictions need to be synthesized to design concepts. During this step, engineers typically rely on their experience and proven practice. Design optimization usually is achieved through an iterative and time-consuming process of analyzing and tuning towards an optimization objective. In this paper a time-saving, automated and systematic method for the design of weight optimized helical gearboxes is proposed. The underlying method has been derived from both, norms and guidelines, which exist for the design and layout of shafts, bearings and gear wheel bodies. Starting with only few input parameters, a detailed shaft geometry with different diameter sections can be derived. A discrete set of values from standard tables and rolling bearing catalogs represents the method’s framework for all realizable shaft diameters in each section. A mixed integer nonlinear optimization problem results from the interdependence between these distinct values. For this purpose, a systematic iterative approach has been developed and implemented in an established design program for gearbox systems. The algorithm uses the results drawn from an analytical calculation of the shaft load carrying capacity to directly adjust the shaft’s diameter and length values. The dimensioning of the wheel body, the service life calculation of rolling element bearings and the selection of specific machine elements are embedded in a systematic sequence. As a result, the model is capable to work out a weight-optimized gearbox that consists of gear meshes, shafts and bearings, taking all three components into consideration at a time.